Factors associated with retention in Option B+ in Malawi: a case control study. Issue 1 (1st January 2017) - Hoffman, Risa M; Phiri, Khumbo; Parent, Julie; Grotts, Jonathan; Elashoff, David; Kawale, Paul; Yeatman, Sara; Currier, Judith S; Schooley, Alan
Abstract: Introduction : There are limited data on factors associated with retention in Option B+. We sought to explore the characteristics of women retained in Option B+ in Malawi, with a focus on the role of HIV disclosure, awareness of partner HIV status, and knowledge around the importance of Option B+ for maternal–child health. Methods : We performed a case‐control study of HIV‐infected women in Malawi initiated on antiretroviral therapy (ART) under Option B+. Cases were enrolled if they met criteria for default from Option B+ (out of ART for >60 days), and controls were enrolled in approximately 3:1 ratio if they were retained in care for at least 12 months. We surveyed socio‐demographic characteristics, HIV disclosure and awareness of partner HIV status, self‐report about receiving pre‐ART education, and knowledge of Option B+. Univariate logistic regression was performed to determine factors associated with retention. Multivariate logistic regression model was used to evaluate the relationship between HIV disclosure, Option B+ knowledge, and retention after adjusting for age, schooling, and travel time to clinic. Results : We enrolled 50 cases and 153 controls. Median age was 30 years (interquartile range (IQR) 25–34), and the majority (82%) initiated ART during pregnancy at a median gestational age of 24 weeks (IQR 16–28). Ninety‐one per cent of the cases (39/43) who started ART during pregnancy defaulted by three months postpartum. HIV disclosure to the primary sex partner was more common among women retained in care (100% versus 78%, p  < 0.001). Odds of retention were significantly higher among women with: age >25 years (odds ratio (OR) 2.44), completion of primary school (OR 3.06), awareness of partner HIV status (OR 5.20), pre‐ART education (OR 6.17), higher number of correct answers to Option B+ knowledge questions (OR 1.82), and support while taking ART (OR 3.65). Pre‐ART education and knowledge were significantly correlated ( r  = 0.43, p  < 0.001). In multivariate analysis, awareness of partner HIV status (OR 4.07, 95% confidence interval (CI) 1.51–10.94, p  = 0.02) and Option B+ knowledge (OR 1.60, 95% CI 1.15–2.23, p  = 0.004) remained associated with retention. Conclusions : Interventions that address partner disclosure and strengthen pre‐ART education around the benefits of ART for maternal and child health should be evaluated to improve retention in Malawi's Option B+ programme.